Trigeminal Neuralgia - where are we today? - Michał Perszke; Dominika Egierska; Patrycja Martynowicz (Kazimierz Wielki University, 2022)
Introduction: Trigeminal neuralgia (TN) is one of the most crippling facial pain syndromes, which has a significant impact on quality of life. This chronic disorder presents as brief shock-like paroxysmal severe, stabbing pain with rapid onset in the distribution of trigeminal nerve (CNV). The aim of this article was to review the recent literature about the epidemiology, pathogenesis, diagnosis, treatment methods and the important advances in all these fields. Etiology and pathomechanism: The best known and tested theory on the genesis of the trigeminal neuralgia seems to be a nerve compression at the nerve root entry-zone. However there are other theories like the trigeminal convergence-projection theory, the bioresonance hypothesis or the ignition theory that are trying to explain the etiology of TN. Treatment: Available treatment methods consist mainly of medications and surgical procedures. Surgical treatment may be divided into 2 categories: destructive and non-destructive. Among these interventions we can distinguish percutaneous rhizotomy stereotactic radiosurgery and microvascular decompression. All of them are very efficacious, however MVD is approved as the gold standard in the treatment of TN. Botulinum neurotoxin  type A injections are not the first line for treatment, but it may be an attractive alternative for classic pharmaceutical or surgical therapy, as it's safe and effective. Acupuncture is also proposed in recent studies as a valuable treatment option, even though there is little well-designed research. Conclusion: Much remains to be learned about the diagnosis, pathomechanism and methods of treatment of neuropathic pain and the efficacy of each of them. Further evidence-based studies are needed, as the amount of reliable materials is still not sufficient and lots of them have yet to be examined.